Business continuity, disaster readiness and performance in COVID-19 outbreak aftermath: A survey. Issue 10 (2022) - Baz, Jamal EL; Ruel, Salomée
Abstract: Anchored in the COVID-19 context, this research seeks to examine the role of business continuity practices in improving both disaster readiness and business performance. A survey of 322 French firms was conducted and data were analyzed using structural equation modelling. The findings corroborate the postulates of resource-based view and organizational information processing theories regarding business continuity practices in COVID-19 context. Firms that improve their disaster readiness ( B = .243; p-value=.008**) and their business continuity practices ( B =.173; p-value=.038*) are more capable of enhancing their performance. The findings raise some questions regarding the validity of the preexisting knowledge on business continuity and disaster readiness in the context of COVID-19.